Diabetes and Obesity Associated with Poor Food Environments in American Indian Communities: the Tribal Health and Resilience in Vulnerable Environments (THRIVE) Study. (5th December 2018) - Love, Charlotte V; Taniguchi, Tori E; Williams, Mary B; Noonan, Carolyn J; Wetherill, Marianna S; Salvatore, Alicia L; Jacob, Tvli; Cannady, Tamela K; Standridge, Joy; Spiegel, Jennifer; Jernigan, Valarie Blue Bird
ABSTRACT: Background: American Indians (AIs) have significantly higher rates of diet-related chronic diseases than other racial/ethnic groups, and many live in environments with limited access to healthy food. Objective: As part of the Tribal Resilience in Vulnerable Environments (THRIVE) study, we examined the relations between the perceived food environment, utilization of food retailers, fruit and vegetable intake, and chronic diseases, including obesity, hypertension, and type 2 diabetes among AI adults. Methods: Through a community-based participatory research partnership, we surveyed a cross-sectional sample of 513 AIs living within the Chickasaw Nation and the Choctaw Nation of Oklahoma. Results: Only 57% of participants reported that it was easy to purchase fruits and vegetables in their town, and fewer (35%) reported that available fruits and vegetables were of high quality. Additionally, over half (56%) reported traveling ≥20 miles round trip to shop for food. Few participants met the recommended daily intake for fruit (44%) or vegetables (25%). Obesity (55%), hypertension (49%), and diabetes (25%) were commonly reported. Obesity was significantly higher among participants who reported that the price of fruits and vegetables were cost-prohibitive (prevalence proportion ratio (PPR): 1.24; 95% CI: 1.02, 1.50) and those who shopped frequently for food at nontraditional food retailers, such as Dollar Stores (PPR: 1.35; 95% CI: 1.08, 1.69) and small markets (PPR: 1.38; 95% CI: 1.02, 1.86). Diabetes was significantly higher among participants who frequently shopped at convenience stores/gas stations (PPR: 2.26; 95% CI: 1.22, 4.19). Conclusions: Our study found that the use of nontraditional food retailers, including convenience stores, gas stations, and Dollar Stores, as a regular source of food was associated with obesity and diabetes. These results underscore the importance of interventions to improve rural Tribal food environments. Healthy retail interventions in nontraditional retail settings, such as those implemented through the THRIVE study, may contribute to reducing AI health disparities.